KEBIJAKAN PENGELOLAAN MIGRASI DALAM KONTEKS PERUBAHAN IKLIM: KASUS LOMBOK UTARA DAN LOMBOK TIMUR - Ade Latifa; Haning Romdiati (Research Centre for Population, Indonesian Institute of Sciences, 2017)
Programs of climate change adaptation strategy and policies related to human migration as a consequence of climate change are needed to facilitate the optimization of environmental migrants. This study aims to examine the response to the impact of climate changes in the context of migration management by the central and local governments. Data for this article are based on the study of the Research Center of Population - LIPI on migration and climate change in North Lombok and East Lombok. The study used a qualitative approach with in-depth interviews and focus group discussions. The results of this study show that migration management policies or programs that are specially prepared to address the impacts of climate change have not yet formulated, neither at the provincial or district levels. The existing migration management policies are more related to efforts to reduce unemployment problems, improve the welfare of Indonesian workers abroad as well as the quality of their lives. Therefore, the provincial government of West Nusa Tenggara needs to respond this situation by formulating migration management policies and programs in the context of climate change, mainly related to the climate change adaptation activities. The plan should be designed to build resilience and adaptation capacity to overcome the adverse impacts of climate change.